Variasi Konsonan Bahasa Jawa pada Masyarakat Kelas Bawah di Daerah Istimewa Yogyakarta - Zultiyanti Zulti (Edukasi Lingua Sastra, 2022)
This study aims to determine the variation of Javanese consonants in the lower-class community in RT 34-35 Giwangan Village, Umbulharjo District, Special Region of Yogyakarta. This type of research is a case study, data obtained utilizing interviews and literature study. The study results indicate that there are variations in consonants that occur in the lower society. The consonant variations are a form of neutral in the word pairs /b/ and /p/, which occurs in the word "landep", which means sharp; in the word pairs /d/ and /t/ occurs in the word "reged" which in Indonesian means dirty, and the word pairs /g/ and /k/ occurs in the word "ambleg" which means to fall. The next variation is the insertion and addition of consonants /n/, /ŋ/, and /m/in the word "montor", which means motorbikes. The next variation is the insertion of semi-vowels /w/ and /y/, which occurs in the word "kebuwang", which means wasted, and in the word "lagèYane", which has the meaning of style. The next variation is the variation of the consonants /z/, /dz/ and /v/, /f/ that occurs in the word "jikir", which means remembrance and the word TV, which is pronounced by with the word "tipi". Next is a shortening variation that occurs in the sentence "no money", which is pronounced by "ra de det" or "ora nduwe duwit". The last consonant variation is the omission of sounds that occur in the word "government", which means government.